HUBUNGAN FAKTOR PEKERJAAN DAN KARAKTERISTIK INDIVIDU TERHADAP TINGKAT KEJENUHAN KERJA PADA KARYAWAN PT XYZ DI BEKASI TAHUN 2023 - Shafa Habsah, (2023)
Burnout is a continuous individual stress condition due to emotional and physical exhaustion. Burnout influenced by work factors such as mental workload and co-worker support, then individual factors such as age, sex, marital status, education level and years of service. Job burnout that was not handled properly could have an impact on decreasing productivity and detrimental effects to the company and the employees themselves. This research aims to determine the association between job factors and individual characteristics with job-burnout among XYZ LLC employees in Bekasi. The samples were 88 workers and selected by accidental sampling technique. The research instruments used were the NASA-TLX questionnaire, the NIOSH Generic Job Stress Questionnaire and the M-TBI (The Maslach-Trisni Burnout Inventory). The results showed that 52.3% of workers experienced high job burnout and there was a significant association between co-worker support and job burnout (P = 0.021, POR 4.08, 95% CI: 0.29-1.70). XYZ LLC is advised to improve positive relations between employees and seniors in order to improve their sense of caring and solidarity to prevent stress and support curative efforts.